Does Lymphadenectomy Improve Survival in Uterine Leiomyosarcoma?. Issue 6 (July 2015) - Tasci, Tolga; Karalok, Alper; Taskin, Salih; Ureyen, Isin; Kimyon, Gunsu; Tulek, Firat; Ozfuttu, Ahmet; Turan, Taner; Tulunay, Gokhan; Kose, M. Faruk; Ortac, Firat
<x xml:space="preserve">Abstract</x> Introduction The role of lymphadenectomy in the management of uterine leiomyosarcoma (LMS) is controversial. We aimed to identify whether lymph node dissection (LND) has any survival benefit in uterine LMS. Methods Data of 95 patients with histologically proven uterine LMS from 2 tertiary centers (1993 through 2009) were retrospectively analyzed. Kaplan-Meier and Cox proportional hazards regression models were used for analyses. Results Mean age was 51.5 years. Thirty-six (37.9%) underwent LND. The median lymph node count was 54. Eight (22.2%) patients had lymphatic metastasis. Median follow-up was 26 months. Sixty-two (65%) patients had recurrence and 48 (50.5%) died. Median disease-free survival (DFS) was 19 months for both group of patients who had or did not have LND, and median overall survival (OS) was 29 and 26 months, respectively (P = 0.4). Five-year DFS was 35.9% vs 26.8% (P = 0.4), and 5-year OS was 45.4% vs 43.8% (P = 0.22) for the groups. Multivariate analyses did not reveal a single independent prognostic factor in respect to DFS or OS. Conclusion Higher rate of lymph node metastasis in patients with extrauterine disease indicated the importance of LND in LMS. However, the survival benefit of lymphadenectomy could not be shown.